European stakeholders’ perspectives on achieving more sustainable wheat cultivation across different pedoclimatic zones - Morugán-Coronado, Alicia; Calatrava, Javier; Meno, Laura; Alonso-Vega, Flora; Pouta, Eija; Tienhaara, Annika; Schrader, Stefan; Bind, David-Alexander; Wustenberghs, Hilde; Fleerakkers, Sander; Fernández-Calviño, David; Gómez-López, María Dolores (Frontiers in Sustainable Food Systems, 2025)
IntroductionSignificant socio-agronomic challenges in wheat production have been revealed in recent years. Soil and nutrient depletion, combined with pest and disease outbreaks, have led to extensive external fertilizer and pesticide use. That situation exacerbates environmental pollution, biodiversity loss, and increases production costs.MethodsThis research identified particularly relevant current agro-environmental problems, barriers and priorities regarding the requirements of end users in wheat cropping systems. A survey was conducted, listing agronomic problems and farming practices. Stakeholders from five European pedoclimatic zones participated in the survey. Their responses were analyzed using univariate statistical techniques and multicriteria methodology. Subsequently, discussion groups with stakeholders were programmed to show, validate, and supplement the survey data.Results and discussionThe study’s findings underscore the need for enhanced learning and training, increased government support, and more enabling legislation to foster implementation of sustainable farming practices. Soil and nutrient loss, coupled with pest and disease incidence are contributing to widespread application of external fertilizers and pesticides that directly leads to environmental pollution, biodiversity loss and increased production costs. To address those issues, agricultural systems must adopt sustainable alternatives such as sustainable agriculture, resilient farming systems, and successful rural communities, avoiding resource depletion, as well as providing ecosystem services.